2013
DOI: 10.1021/ja408787k
|View full text |Cite
|
Sign up to set email alerts
|

Two-Electron HCl to H2 Photocycle Promoted by Ni(II) Polypyridyl Halide Complexes

Abstract: Photochemical HX splitting requires the management of two protons and the execution of multielectron photoreactions. Herein, we report a photoinduced two-electron reduction of a polypyridyl Ni(II) chloride complex that provides a route to H2 evolution from HCl. The excited states of Ni complexes are too short to participate directly in HX activation, and hence, the excited state of a photoredox mediator is exploited for the activation of HX at the Ni(II) center. Nanosecond transient absorption (TA) spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 60 publications
3
58
0
Order By: Relevance
“…Biphenyl was also observed as a product. Although attempts to crystallize 4 were unsuccessful, the 1 H NMR spectrum is similar to the previously reported homoleptic complex [(neocuproine) 2 Ni I ](PF 6 ), and the EPR spectrum is consistent with a metal‐centered radical with axial geometry. Mass spectrometry indicates the presence of a cationic, [(neocuproine) 2 Ni I ] unit.…”
Section: Methodssupporting
confidence: 75%
See 1 more Smart Citation
“…Biphenyl was also observed as a product. Although attempts to crystallize 4 were unsuccessful, the 1 H NMR spectrum is similar to the previously reported homoleptic complex [(neocuproine) 2 Ni I ](PF 6 ), and the EPR spectrum is consistent with a metal‐centered radical with axial geometry. Mass spectrometry indicates the presence of a cationic, [(neocuproine) 2 Ni I ] unit.…”
Section: Methodssupporting
confidence: 75%
“…Similar electronic configurations were observed in terpyridine‐ligated Ni I complexes . This configuration, however, is different to the only other known bidentate polypyridyl‐containing Ni I species, which are cationic homoleptic complexes of phenanthroline derivatives that contain a metal‐centered radical . It is also intriguing that 1 is formed through a reaction with a common sp 2 ‐electrophile, as it raises the possibility that previously unobserved dinuclear species could be present in catalysis.…”
Section: Methodsmentioning
confidence: 86%
“…As shown, 3a-D was prepared in high yields from either (CD 3 ) 2 CHBr or (CH 3 ) 2 CDBr with 75% and 15%-D content, respectively, suggesting that a b-hydride elimination/migratory insertion might occur at some extent prior to alkyne binding. 22 The stoichiomeric experiments with Ni(L4) 2 are particularly illustrative (Scheme 3, bottom); 23 specifically, we found that 3a was solely obtained in the presence of i-PrBr, thus ruling out an oxidative cyclization of Ni(0), 1a and 2a en route to I. 6 Although further studies are needed, we currently propose a pathway consisting of a hydrometalation with in situ generated Ni(II)-hydride, single electron transfer (SET) mediated by Mn en route to a Ni(I) intermediate 24 followed by RNCO insertion 25 and a final SET to recover the Ni(0) species.…”
Section: Scheme 2 Synthetic Applicabilitymentioning
confidence: 99%
“…Although a comprehensive study detailing the mechanistic underpinnings of this reaction will require further investigations, we decided to study the reactivity of Ni 0 ( L4 ) 2 ( 5 ) and Ni I ( L4 ) 2 compounds ( 6 ). While 18‐electron complex 5 was prepared in quantitative yield by reacting Ni(COD) 2 and L4 in benzene at 40 °C, complex 6 was prepared from 5 upon exposure to AgOTf in THF at RT . As shown in Scheme , both structures were unambiguously characterized by X‐ray crystallography .…”
Section: Methodsmentioning
confidence: 99%